2006
DOI: 10.1055/s-2005-921752
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 5-Acyl-2-amino-1,3-selenazoles by the Reaction of Selenazadienes with α-Haloketone

Abstract: Reaction of selenazadienes with a-haloketones gave 5-acyl-2-amino-1,3-selenazoles in high yields.Many syntheses of selenium-containing heterocyclic compounds have been reported because of their interesting reactivities 1 and potential biological interest. 2 For example, 1,3-selenazole derivatives inhibit lipopolysaccharideinduced nitric oxide production in BV-2 cells. From structure-activity relationships, specific substituent groups on the 1,3-seleazole skeleton have been shown to strongly influence the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…17) A Cypridina luciferin analogue, 2-methyl-6-(4-methoxyphenyl)-3,7-dihydroimidazo-[1,2-a]-pyrazin-3-one hydrochloride (MCLA) was obtained from Tokyo Kasei (Tokyo, Japan) for a use as a chemiluminescent probe for superoxide radicals. MCLA was dissolved in doubly distilled water and stored at Ϫ80°C prior to usage.…”
Section: Methodsmentioning
confidence: 99%
“…17) A Cypridina luciferin analogue, 2-methyl-6-(4-methoxyphenyl)-3,7-dihydroimidazo-[1,2-a]-pyrazin-3-one hydrochloride (MCLA) was obtained from Tokyo Kasei (Tokyo, Japan) for a use as a chemiluminescent probe for superoxide radicals. MCLA was dissolved in doubly distilled water and stored at Ϫ80°C prior to usage.…”
Section: Methodsmentioning
confidence: 99%
“…Hantzsch condensation can be considered the most employed method for the preparation of 1,3‐selenazoles [238] . A metal‐free decarboxylative cyclization of 2‐chloronitrobenzene, arylacetic acids, and elemental selenium to prepare 2‐phenylbenzoselenazoles of formula 275 has been recently described [239] .…”
Section: Chemistrymentioning
confidence: 99%
“…[229] Hantzsch condensation can be considered the most employed method for the preparation of 1,3-selenazoles. [238] A metal-free decarboxylative cyclization of 2-chloronitrobenzene, arylacetic acids, and elemental selenium to prepare 2-phenylbenzoselenazoles of formula 275 has been recently described. [239] The optimized reaction conditions indicated that this multi-component transformation worked better when Nmethylpiperidine was chosen as the solvent, with the optimal temperature being 130 °C for 24 h. It was observed a negative effect on the reaction yield when this transformation was conducted in the presence of air.…”
Section: Selenium-containing Heterocycles and Ebselenmentioning
confidence: 99%
“…Unlike N,N-disubstituted selenoureas 14 carbonyl chlorides 84 which were treated with water, alcohols, or amines [120,121] (Scheme 24). A simple one-pot procedure for the synthesis of 5-acyl-2-amino-1,3-selenazoles 86 in high yield from selenazadienes 22 and α-haloketones was reported [122]. Analogous reaction of 22 with 1,3-dichloropropan-2-one afforded bis(2-amino-1,3-selenazol-5-yl)methanones 87 (Scheme 24).…”
Section: Scheme 19mentioning
confidence: 99%